Mengoptimalkan Nilai-Nilai Pancasila Selama dan Sesudah Pandemi Covid-19 [Optimizing the Values of Pancasila During dan After the Covid-19 Pandemic] - Kristina Untari Setiawan (Universitas Pelita Harapan, 2020)
During the pandemic of COVID-19 that has stricken almost the whole world, including Indonesia, Pancasila as Indonesia’s solid foundation should and could be implemented in the effort of reducing anxiety and fear among the people. When practiced wholeheartedly, the five principles are effective weapons to combat every obstacle caused by COVID-19. The challenges of being different in term of race, religion, and culture may not be impossible to handle because Pancasila lives in the heart of the people of Indonesia. This article aims to see each sila as our guidance in facing the pandemic that may still threaten humanity in the next several months, as well as encouraging us to learn and be transformed, seeing the future with optimism. Optimism, which can take the value of unity in diversity, will give great hope for all components in the society, when we as citizens are able to integrate the values with our character.